Disaster upon disaster : exploring the gap between knowledge, policy, and practice - Hoffman, Susanna M.; Barrios, Roberto E. (New York : Berghahn Books, 2020)
"A consistent problem that confronts disaster reduction is the disjunction between academic and expert knowledge and policies and practices of agencies mandated to deal with the concern. Although a great deal of knowledge has been acquired regarding many aspects of the gap, such as driving factors, risk construction, complexity of resettlement, and importance of peoples' culture, very little has gotten into protocol and procedure. Disaster Upon Disaster illuminates the numerous disjunctions between the suppositions, realities, agendas, and executions in the field, goes on to detail contingencies, predicaments, old and new plights, and finally advances solutions and the matter of outcomes"--
Includes bibliographical references and index.
Keywords: Disasters -- Social aspects; Disaster relief -- Social aspects; Emergency management -- Social aspects